Hydrogeology and Hydrogeochemistry of the Lauria Mountains Northern Sector Groundwater Resources (Basilicata, Italy) - Filomena Canora; Giovanna Rizzo; Simona Panariello; Francesco Sdao (Geofluids)
In this study, the hydrogeological characterization of the northern sector of the Lauria Mounts carbonate hydrostructure (southern Apennines, Basilicata region) has been carried out and the hydrochemical properties of different collected groundwater samples have been characterized. Several normal springs drain the hydrostructure, some of them characterized by high annual mean discharges. Groundwater samples were collected from different springs; many parameters such as pH, electrical conductivity, and total dissolved solids have been measured, and major (cations and anions) elements and stable isotopes have been analysed following standard test procedures. Other chemical characteristics were derived from the analysed quality parameters. The results elucidate that the main hydrogeochemical processes control the chemical content and assess the quality of the groundwater within the hydrostructure. The analyses highlight that the chemical compositions of groundwater are strongly influenced by the lithology, especially limestones and dolomitic limestones; they explain and confirm the hydrogeological setting of the system. The groundwater system displays light different geochemical signatures. The processes contributing to the concentrations of major ions depend primarily on carbonate dissolution. The analysis, in all studied groundwater samples, shows that the facies groundwater type is Ca–HCO3, bicarbonate is the dominant anion, and calcium is the dominant cation with appreciable magnesium concentrations. To identify the aquifer’s recharge areas, the environmental stable isotopes oxygen and hydrogen, deuterium, and 18O were analysed. The unaltered δ18O and δD signatures for the groundwater of the major springs allows identifying the recharge area of these emergencies at elevations ranging from 900 m to 1000 m (a.s.l.), pointing out the presence of deeper flow regime feeding of these springs. The groundwater sample isotopic characteristics of D and 18O suggest that most of the groundwater is recharged directly by infiltration in a high-permeability medium.